2015
DOI: 10.1186/s12876-015-0244-z
|View full text |Cite
|
Sign up to set email alerts
|

Does lower gastrointestinal endoscopy during pregnancy pose a risk for mother and child? – a systematic review

Abstract: BackgroundGastrointestinal endoscopy plays a crucial role in the diagnosis and management of gastrointestinal disorders. When endoscopy is indicated during pregnancy, concerns about the effects on pregnancy outcome often arise. The aim of this study was to assess whether lower gastrointestinal endoscopies (LGEs) across all three trimesters of pregnancy affects pregnancy outcomes.MethodsA systematic literature search was performed using Embase (including MEDLINE), Medline OvidSP, Cochrane Central Register of Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 78 publications
0
19
0
3
Order By: Relevance
“…The investigators suggested that lower gastrointestinal endoscopy is likely safe to perform throughout all 3 trimesters of pregnancy. 164 This is further supported by a recent prospective cohort study in which 42 pregnant patients with IBD underwent lower gastrointestinal endoscopy, with no increased adverse outcomes for the mother or the newborn related to endoscopy. 165 Although 2 spontaneous abortions were temporally and probably related to endoscopy, the overall rate of spontaneous abortion was lower in cases than in controls (4.8% vs 23.8%; P ¼ .01).…”
Section: Medical Management Of Ibd During Pregnancymentioning
confidence: 70%
See 1 more Smart Citation
“…The investigators suggested that lower gastrointestinal endoscopy is likely safe to perform throughout all 3 trimesters of pregnancy. 164 This is further supported by a recent prospective cohort study in which 42 pregnant patients with IBD underwent lower gastrointestinal endoscopy, with no increased adverse outcomes for the mother or the newborn related to endoscopy. 165 Although 2 spontaneous abortions were temporally and probably related to endoscopy, the overall rate of spontaneous abortion was lower in cases than in controls (4.8% vs 23.8%; P ¼ .01).…”
Section: Medical Management Of Ibd During Pregnancymentioning
confidence: 70%
“…163 A systematic review of controlled trials, cohort studies, and case series reported on the outcomes of 100 lower gastrointestinal endoscopies performed in all 3 trimesters of pregnancy. 164 Six adverse events were classified as related to the procedure: 3 with flexible sigmoidoscopy (incomplete spontaneous abortion, fetal death, and suspected perforation leading to emergency cesarean delivery) and 3 with colonoscopy (fetal death, pregnancy termination by physicians, and premature spontaneous labor). All but one of these events was classified as probably or possibly related to the procedure but could have been related to another intervention performed at the time or the underlying maternal disease.…”
Section: Medical Management Of Ibd During Pregnancymentioning
confidence: 99%
“…Colonoscopy may be indicated in a pregnancy state, to evaluate the extent of ulcerative colitis that may determine the need for additional immunosuppressive agents or in small bowel Crohn’s disease. A systematic review of lower gastrointestinal endoscopies performed in all three trimesters of pregnancy evaluated any adverse pregnancy outcomes that were noted to be in a temporal or etiological relation with the procedure[ 12 ]. This review comprised of 100 endoscopies, with a total of six reported adverse events that were related to the procedure.…”
Section: Lower Endoscopymentioning
confidence: 99%
“…Thus, only few studies assess pH parameters in patients with SSc. Abnormal pH monitoring has been seen in up to 85% of patients [ 33 - 35 ]. Although the number of reflux events is similar between SSc patients and non-scleroderma patients, a small but well-designed study [ 36 ] found that SSc patients showed a greater number of events with longer duration.…”
Section: Diagnosismentioning
confidence: 99%